Simulation heart beat monitoring system - Ong, Kah Siang (2010)
Simulation Heart Beat Monitoring System (SHBMS) is a system which applies technique of signal processing. First of all, the input shall be digitalized into a form which understands by the machine before start analyzing: it. Then, the tool used to develop SHBMS is Visual Studio 6 (VB6). There is a libcary available and able to embed into V136 in handling the input and generate output in waveforin signal. In SHBMS, a simulation input such as audio file of heart beat or beats on microphone shall be used to replace a real heart beat from a human being. The idea of using simulation input is due to the difficulty of capturing real heart beat using a sensor or device. Yet, the SHBMS still able to detect input and react according to the input. The output is generated according to the size of byte (beat per minute) and shall give comment upon the size of byte. Furthermore, waveform signal shall be displayed as well to show the changes of the signal which high or low. This indicates the signal of the heartbeat. Moreover, SHBMS is developing according to Software Development Life Cycle process and able to finish within the proposed period.